Partnership Model For Optimizing The Use of Village Funds - Mukhtar Sarman (Iapa Proceedings Conference, 2018)
Since 2015, the Government has allocated village development funds in the form of Village Fund policies of IDR 20.7 trillion, then in 2016 it increased to IDR 46.9 trillion, and continues to increase in the following years. However, based on field research in a number of regions in Indonesia, it turns out that the use of Village Funds is not optimal, some of which have been proven wrongly targeted, not transparent in use, and not accountable in reporting. The aspect of planning activities and the quality of human resources implementing policies and coordination between parties that should play a role are still a major problem. The PPP (Public-Private Partnership) model is actually intended for the development of large-scale projects, such as the construction of highways or seaports and airports. But by taking the substance of cooperation from the parties that each have strengths, the PPP model (and its variants) may be applicable in the use of Village Funds. Using secondary data analysts, the following article discusses the theoretical aspects of the advantages of the PPP model. This model is juxtaposed with cases of success in building the economic self-reliance of rural communities with the help of private parties and academics. It is assumed that the partnership model can be an alternative solution to further optimize the use of Village Funds in order to reduce poverty in rural areas.